Preparation and Evaluation of Tetrandrine Nanocrystals to Improve Bioavailability - Xue, Fei; Yang, Lan; Ma, Shuai; Chang, Jin hua; Liu, Pei; Liu, Xi Gang; Wang, Ru xing (Current Drug Delivery, 2025)
Introduction/Background Tetrandrine (TET) has multiple pharmacological activities, but its water solubility is poor, which is the main reason for its low bioavailability. Objectives The purpose of this study was to prepare TET nanocrystals (TET-NCs) using a grinding method to enhance the dissolution rate and ultimately improve the bioavailability of TET. Methods TET-NCs were synthesized via media milling, employing Poloxam 407 (P407) as surface stabilizer and mannitol as a cryoprotectant during freeze-drying. The crystal structure, particle diameter, and zeta potential were characterized using differential scanning calorimetry (DSC), Fourier-transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), and X-ray diffraction (XRD). The in vitro release behavior and pharmacokinetics of TET-NCs were assessed. The cytotoxicity of TET and TET-NCS on RAW264.7 cells was determined by the CCK-8 method. Results The particle size of TET-NCs was 360.0±7.03 nm, PDI was 0.26±0.03, and zeta potential was 6.64±0.22 mV. The cumulative dissolution within 60 minutes was 96.40±2.31%. The pharmacokinetic study showed that AUC0-72 h and Cmax of TET-NCs were significantly enhanced by 3.07 and 2.57 times, respectively, compared with TET (p<0.01). TET-NCs significantly increased the cell inhibition on RAW264.7 cells compared to the TET (P<0.01). Conclusion The preparation of TET-NCs enhanced dissolution rate and bioavailability significantly, and it also improved the inhibition effect of RAW264.7 cells.
Keywords: pharmacokinetics